Korelasi Kekakuan Arteri Dengan Kadar Endothelin-1 Plasma pada Laki-laki Obesitas - Adrianus Kosasih; Oktavia Lilyasari; Richard Indra Gunawan; Nur Haryono; Ismoyo Sunu (The Indonesian Heart Association, 2007)
Background.Obesity is associated with increase arterial stiffness and el-evated plasma endothelin-1 concentration. However, there is still conflict-ing data regarding the effect of obesity on arterial stiffness and plasma endothelin-1 concentration.Objective.The purpose of the current study was to assess this effect and analyze whether there was correlation between arterial stiffness indices and plasma endothelin-1 concentration.Methods.The design of the study was cross sectional study that compare and correlate arterial stiffness and plasma endothelin-1 concentration be-tween obesity group (n=40) and normoweight group (n=40). Obesity was defined as body mass index = 25 kg/m2. Arterial stiffness was as-sessed by measuring carotid-femoral pulse wave velocity (PWV) dan ß stiffness index (ß) non-invasively using ultrasound method. Endothelin-1 was measured by ELISA.Results.There was no significant difference regarding PWV between obesity and normoweight group (mean ± SD: 809.44 ± 137.77 versus 850.96 ± 211.60 cm/s, p=NS), but ßwas significantly higher in obese group (8.79 ± 3.15 versus 7.28 ± 1.96, p=0.012). PWV and ßcorre-lated significantly with age (PWV: r=0.446, p<0.001, ß: r=0.354, p=0.001), but only ßcorrelated with body mass index (r=0.282, p=0.011) and waist circumference (r=0.312, p=0.005). There was no significant difference between obesity and normoweight group regard-ing plasma endothelin-1 concentration (0.94 ± 0.26 versus 0.95 ± 0.18 pg/dl, p=NS). There are no significant correlations between PWV/ßand plasma endothelin-1 concentration.Conclusions.These findings suggest that the effect of obesity on arterial stiffness is not uniformly seen throughout all arterial region. Obesity im-pact on carotid artery is greater than its impact on aorta, and this impact on arterial stiffness is not mediated by endothelin-1.